The role of the cysteine-rich domain of Frizzled in Wingless-Armadillo signaling. - Povelones, M.; Nusse, R. (The EMBO Journal, 2005)
The Frizzled (Fz) receptors contain seven transmembrane helices and an amino-terminal cysteine-rich domain (CRD) that is sufficient and necessary for binding of the ligands, the Wnts. Recent genetic experiments have suggested, however, that the CRD is dispensable for signaling. We engineered fz CRD mutant transgenes and tested them for Wg signaling activity. None of the mutants was functional in cell culture or could fully replace fz in vivo. We also show that replacing the CRD with a structurally distinct Wnt-binding domain, the Wnt inhibitory factor, reconstitutes a functional Wg receptor. We therefore hypothesized that the function of the CRD is to bring Wg in close proximity with the membrane portion of the receptor. We tested this model by substituting Wg itself for the CRD, a manipulation that results in a constitutively active receptor. We propose that Fz activates signaling in two steps: Fz uses its CRD to capture Wg, and once bound Wg interacts with the membrane portion of the receptor to initiate signaling.